Implementasi Model Problem Based Learning Berbantuan Multimedia Di Sekolah Dasar - A Arsil (Department of Primary School Teacher Education, Faculty of Teacher Training and Education, Jambi University, 2019)
The purpose of this study is to describe the implementation of multimedia-assisted problem based learning in elementary schools. This type of research is qualitative descriptive. The place of research is SDN 64 / I Muara Bulian, the research subject is class V students. The research procedures are data collection, data reduction, data display and conclusion drawing. Data collection techniques: Observation and Interview. The results of the study, namely the implementation of a multimedia-based problem based learning model, is very helpful for students in carrying out problem solving activities. Science materials presented through learning videos are more interesting and arouse students' interest in learning. However, the obstacle faced by teachers is the difficulty of formulating problems in science materials and looking for learning resources in the form of learning videos that are suitable for learning. So that as a teacher of course must be creative in creating problem solving activities, considering problem solving is one aspect that students must have in the 21st century.